Effect of biochar addition on the OFMSW composting process under real conditions - Malinowski, Mateusz; Wolny-Koładka, Katarzyna; Vaverková, Magdalena Daria (Waste management (New York, N.Y.), 2019)
The article evaluates the effect of small selected doses of biochar addition (0%, 1.5%, 3% and 5%, wet weight) on the composting process of the organic fraction of municipal solid waste (OFMSW) with a low initial C/N ratio under real conditions. The low C/N composting mixtures with addition of biochar at low rates can have a positive effect on the compost quality and on the reduction of N losses in compost. The novelty of this work consists in studying the impact of small biochar doses on the composting process at full-scale. The research was conducted under real conditions in the Brno Central Composting Plant (Czech Republic) receiving food waste, grass, straw, sawdust, mineral waste, paper, wood and sewage sludge for processing. The experimental processing time was 12 weeks. We evaluated changes in carbon (C), nitrogen (N), moisture content (MC), organic matter (OM), respiration activity (AT4), as well as changes in the microbiocenotic composition of microorganisms colonizing the processed waste. OFMSW with the addition of biochar and compost were assessed for the content of heavy metals (HM). It was found out that biochar reduced the compost toxicity. The resulting compost with the addition of biochar exhibited higher moisture content and lower waste density. Biochar had an impact on N retention during composting but it did not change the course or accelerate the composting process. The highest OM loss (62.6%) was observed in the OFMSW with no biochar addition. The abundance of potentially pathogenic microorganisms clearly decreased during the OFMSW composting process with the addition of biochar.
Keywords: kompostování; Phytotoxicity tests; Česká republika; Organic waste; Charcoal; dřevěné a živočišné uhlí; Soil; Biochar; půda; Composting; Czech Republic; Nitrogen; Microorganisms; dusík